Metodologia para análise de geração compartilhada: uma abordagem para investidores em diferentes regiões do Brasil - Cancio, Lucas Dias (2024)
The issues related to global warming and frequent climate changes demand the implementation of measures to mitigate such challenges. To overcome these challenges, it is crucial to incorporate sustainable practices, foster energy efficiency, and explore cleaner and renewable energy sources. Consequently, distributed solar generation has seen a notable increase on a national scale, driven mainly by the growing competitiveness in its segment and the increasing demand for electrical energy. The high tariffs practiced by energy utilities have significant impacts on the lives of energy consumers. Therefore, shared energy generation in Brazil promotes inclusion and democratization of access to distributed generation, thanks to facilitating business models, regardless of financial conditions or available space for installation. Thus, the objective is to present a modeling of shared generation plants, in the form of plants for lease, covering different regions of Brazil. Through this method, a comprehensive analysis of the implications of the legal framework of distributed generation, with special emphasis on Law 14,300, from the perspective of investors, was sought. The proposed methodology was applied considering a power of 100.98 kWp for the modules, while the power of the inverters was limited to 75 kW/AC, classifying the system as microgeneration. In managing the energy credits generated by the plants, the use of a consortium model was defined. Thus, financial aspects were analyzed, including fluctuations in the return on investment of these plants, through indicators such as the Internal Rate of Return (IRR), Net Present Value (NPV), and the period needed to recover the investment. Through the analysis of the modeling carried out for five different regions of Brazil, it was possible to observe that the change in regulation presents challenges for this type of investment, mainly due to the significant impacts of the costs associated with TUSD Fio B and TUSD G in the calculation of financial return. Furthermore, this transition represents a crucial factor that significantly impacts the investment recovery period in the plant. The impact resulting from the new rules of Law 14,300 applied to the compensation of generated and injected energy into the grid is highlighted compared to the previous regulation. As a preview of the results, Brasília/DF stands out, which even with the new rules imposed by the Law, resulted in more attractive values regarding financial return compared to other regions studied in this research. One of the purposes of this work is to present how profitable an investment plant is in different regions and the impact that regulatory change imposes on these projects.